Pendeposisian Besi pada Subtrat Alumunium dengan Metode Sputtering Terhadap Variasi Suhu - Handoyo Saputro (JPSE (Journal of Physical Science and Engineering), 2016)
The sample was a sputtered iron by aluminium substrate at variations of 60oC to 180oC with 3 hours of deposition time. The research result showed that some colour changing those partially golden yellow mix with red, blue and some of the grey. Micro-hardness was tested using MXT70 model and showed that the maximum hardness level at the temperature of 100oC is 113%. However, at temperature 180oC the hardness level decreased. The resistivity and conductivity were determined by four points probe method. It was known that the resistivity decreases up to (66 ± 3) x 10-5 Ω/m and the conductivity increases (147 ± 65) (Ω/m)-1 at temperature 180oC and they tended to be linear and it has been the best measurement result. DOI: http://dx.doi.org/10.17977/um024v1i12016p029